2017
DOI: 10.1038/s41598-017-15394-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative N-terminal pro-B-type natriuretic peptide concertation and prognosis of brain tumor patients: a 5-year follow up study

Abstract: Increased N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentration predicts poor prognosis of non-CNS cancer patients. We evaluated the association of NT-proBNP concentration with disease severity, discharge outcomes and prognosis of patients undergoing craniotomy for brain tumor. From January, 2010 until September, 2011 two-hundred and forty-five patients (age 55.05 ± 14.62 years) admitted for brain tumor surgery were evaluated for NT-proBNP serum concentration. Outcome at hospital discharge was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Indeed, in our sample, nearly one-third of meningioma patients and 22% of glioma patients presented with cardiovascular comorbidity. In line with previous findings, we found that cardiovascular comorbidity and older age were related to greater NT-proBNP concentrations [25,26], suggesting that NT-proBNP can be a valuable biomarker of underlying cardiovascular function impairment of BT patients. However, Ruggieri et al [18] in a sample of 108 BT patients found no association between increase in NT-proBNP and cardiac dysfunction; levels of NT-proBNP were directly associated with cerebral damage.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, in our sample, nearly one-third of meningioma patients and 22% of glioma patients presented with cardiovascular comorbidity. In line with previous findings, we found that cardiovascular comorbidity and older age were related to greater NT-proBNP concentrations [25,26], suggesting that NT-proBNP can be a valuable biomarker of underlying cardiovascular function impairment of BT patients. However, Ruggieri et al [18] in a sample of 108 BT patients found no association between increase in NT-proBNP and cardiac dysfunction; levels of NT-proBNP were directly associated with cerebral damage.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, only one previous study investigated the relationship between levels of NT-proBNP and cognitive functioning of BT patients. Bunevicius et al found that greater NT-proBNP serum concentrations correlated with general cognitive decline in a mixed sample of BT patients [25]; however, this association was not adjusted for potential cofounders. Similarly, in a sample of stroke patient levels, NT-proBNP at admission was associated with worse cognitive functioning in univariate analysis, but the relationship became nonsignificant when the model was adjusted for age, stroke type, and other clinical variables [34].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1). The possible reason for elevated B-type NP include: comorbid heart failure (HFpEF), chronic kidney disease, central nervous system malignancy itself, and/or hypertensive encephalopathy [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%